anxiety and joy of natal expectation: an analysis of simi kosoko's duduke (2020)
The period of pregnancy is usually a period of deep emotions which an artist may wish to express. The expressive theory of art states that art is a means of portraying unique individual feelings and emotions of an artist, and good art successfully communicates the feelings and emotions of the artist. This article undertakes an analysis of Dùdùke ̩́, a song released by popular Nigerian artist, Simi Kosoko, during the period of her first pregnancy, soon after marriage to equally popular Nigerian artiste Adekunle Gold. Content analysis was employed to examine the feelings and emotions that could have led to the composition of this song by the artist. The song, a manifestation of the artist in a pregnant woman, expresses an analogy between the kick of the bass drum of a trap set and the kick of a foetus as expressed in the title of the song Dùdùke ̩́. Composing the song during the period of her antenatal experience, therefore, showcases Simi as a prolific composer and recording artist who enjoys using her musical talent in expressing her personal feelings and experiences.